A Combined Raman Spectroscopic and Thermogravimetric Analysis Study on Oxidation of Coal with Different Ranks. (23rd November 2015) - Zhang, Weiqing; Jiang, Shuguang; Hardacre, Christopher; Goodrich, Peter; Wang, Kai; Shao, Hao; Wu, Zhengyan
Abstract : Raman spectroscopy and nonisothermal thermogravimetric analysis (TGA) measurements have been reported for different rank coals (lignite, bituminous coal, and anthracite) and the relationship between the measurements was examined. It was found that the Raman spectra parameters can be used to characterize structure changes in the different rank coals, such as the band area ratios based on the curve-fitted results. Higher ranked coal was found to have higher values ofI G R / I A l l andI G + G R / I A l l but lower values ofI D / I ( G + G R ), I D L / I ( G + G R ), I S + S L / I ( G + G R ), andI ( G L + G L ' ) / I ( G + G R ) . The oxidation properties of the coal samples were characterized by the reactivity indexesT i g, T 20 %, andT m a x from TGA data which were found to correlate well with the band area ratios ofI G R / I A l l, I G + G R / I A l l, andI S + S L / I ( G + G R ) . Based on these correlations, the Raman band area ratios were found to correlate with the oxidation activity of coal providing additional structural information which can be used to understand the changes in the TGA measurements.